Development of reactive digital printing process for cellulosic fabrics - Turgut, Halil İbrahim; Girgin, Aslı Balçak; Yarar, Özlem (İdris Karagöz, 2023)
In this study, the development processes of reactive digital printing for cellulosic fabrics are discussed. In the study, viscose fabric qualities were evaluated with the same content and different impregnation process numbers, according to pH value, washing fastness, rubbing fastness, water fastness, and perspiration fastness tests, after digital printing application under the same conditions. In addition, print patterns were visually examined. It has been determined that the visual quality of the fabrics with one pass impregnation is better than two passes impregnations and the test results have similar values for all samples. Viscose fabric qualities, with one pass application, were tested by applying different recipes and the optimum recipe was determined by making a cost analysis and sustainability aspect. It was determined that the wet rubbing fastness values were low. Fabric pH test results were determined to be in the range of 5.5-7.5, as expected. Washing, water, and perspiration fastness values were determined to be in the range of 4-5 as expected.
HRPT-PR-K55
Keywords: Textile Chemistry; Tekstil Kimyası